Застосування LSTM та автоенкодерів у MATLAB для виявлення аномалій у датчикових даних - Столовий, І. В. (ХНУРЕ, 2025)
This paper discusses the application of LSTM models and autoencoders for anomaly detection in biomedical signals, specifically in data from medical sensors. LSTM models, due to their ability to work with time series, allow for efficient learning from signal data and the detection of patterns.
Keywords: автоенкодер; виявлення аномалій у датчикових даних